Online Learning Obstacles for Mathematics Education Students During Pandemic - Salsabila, Nilza Humaira; Lu'luilmaknun, Ulfa; Triutami, Tabita Wahyu; Wulandari, Nourma Pramestie (Al-Khawarizmi, 2021)
The aim of this study is to explain how the obstacles experienced by mathematics education students through online learning during the pandemic. This research is descriptive research. Respondents in this study were students of mathematics education at the University of Mataram, amounting to 126 people. The data in this study were obtained through a questionnaire and analyzed by descriptive statistics. The results showed that most of the obstacles experienced by students were in terms of internet networks and inadequate devices. In addition, students also have difficulty understanding lecture material online and feel that their motivation and interest in learning has decreased during the pandemic.